2021
DOI: 10.1101/2021.06.29.450360
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Using wearable biosensors and ecological momentary assessments for the detection of prolonged stress in real life

Abstract: Emerging efforts toward prevention of stress-related mental disorders have created a need for unobtrusive real-life monitoring of stress-related symptoms. We used ecological momentary assessments (EMA) combined with wearable biosensors to investigate whether these can be used to detect periods of prolonged stress. During stressful high-stake exam (versus control) weeks, participants reported increased negative affect and decreased positive affect. Intriguingly, physiological arousal was decreased on average du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…This measure is novel in capturing inter-individual differences in positive affect changes in response to in-the-moment stress. We focus on positive affect as our previous work has shown that stress seems to have a bigger impact on positive rather than negative affect 31 . This may be due to respondents showing greater variability when answering positive affect items, which is reflected in the skewed distribution of negative affect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This measure is novel in capturing inter-individual differences in positive affect changes in response to in-the-moment stress. We focus on positive affect as our previous work has shown that stress seems to have a bigger impact on positive rather than negative affect 31 . This may be due to respondents showing greater variability when answering positive affect items, which is reflected in the skewed distribution of negative affect.…”
Section: Discussionmentioning
confidence: 99%
“…Within the scope of the current paper, only subjective stress and positive affect measures are used from the EMA data. Full details and results of the EMA weeks are reported in previous work, and the full questionnaire set can be found in the associated GitHub directory 31 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For other stress-related disorders, pinpointing the optimal time for an early intervention might be more difficult, as they are not necessarily triggered by a single event, but can develop more gradually. However, research has suggested that the transition into a mental disorder is foreshadowed by a gradual deterioration of resilience with a slowing-down of stress recovery during repeated exposure to stressors (Nelson et al, 2017), and recent efforts into the detection of early warning signs using ecological momentary assessments and wearables were already successful in predicting dailylife stress (Tutunji et al, 2022) as well as the risk of symptom transitions (Wichers et al, 2020). Targeting individuals before such critical transition points with prospective neurofeedback training will strengthen their resilience to future stressors and has the potential to prevent a progression into stress-related mental illness (see also Figure 3b).…”
Section: Resilience Prevention and Health Maintenancementioning
confidence: 99%
“…stress) and recruited general populations (e.g. college students) were assessed with self-reported questionnaires and commercial wearable devices [6, 69, 78]. Only few previous endeavors specifically addressed mood disorders using clinician assessments.…”
Section: Introductionmentioning
confidence: 99%